Damage evolution of slab tracks with complex temperature distribution - Yang Li; Kailin Cao; Jinjie Chen; Haiyan Li; Zhihao Yang; Guocui Wang (Alexandria Engineering Journal)
High-speed railways extensively utilize longitudinally continuous slab tracks, which are susceptible to significant structural damage caused by temperature change. This study emphasizes the impact of complex temperature distribution characteristics of the tracks on track damage including interfacial debonding, slab end arching and concrete joint failure. Firstly, the nonlinear temperature distribution in track structures was characterized using field measurement data. Secondly, a numerical model of the longitudinally continuous slab track model was tailored and validated. Next, the numerical model was used to investigate the damage evolution of the track caused by its complex nonlinear temperature distribution. Finally, the study thoroughly examined the effects of variations of temperature distribution characteristics on the track's mechanical performance. Results show that: (1) Considering a vertical nonlinearity of 0.3 and a lateral gradient of 10 ℃/m can improve the maximum vertical displacement by 31.6 %. (2) The critical air temperature for interface damage initiation can be approximately 5 ℃ lower when the vertical nonlinearity and the lateral gradient are not considered than when they are considered. The distribution of damage on the interface between track slabs and mortar layers also varies depending on the temperature assumptions. (3) The maximum compression damage of the pre-damaged T-shaped concrete joint decreases with increasing vertical nonlinearity and lateral gradient. These new findings are of significant theoretical importance as they emphasize the need to consider temperature distribution characteristics that have been overlooked in previous studies. Additionally, the insights from this study have practical value as they provide track engineers with a state-of-the-art recommendation for incorporating realistic temperature distribution in the evaluation of longitudinally continuous slab tracks' performance.